Role of Fas and Treg Cells in Fracture Healing as Characterized in the Fas‐Deficient (lpr) Mouse Model of Lupus. (June 2014) - Al‐Sebaei, Maisa O; Daukss, Dana M; Belkina, Anna C; Kakar, Sanjeev; Wigner, Nathan A; Cusher, Daniel; Graves, Dana; Einhorn, Thomas; Morgan, Elise; Gerstenfeld, Louis C
ABSTRACT Previous studies showed that loss of tumor necrosis factor α (TNFα) signaling delayed fracture healing by delaying chondrocyte apoptosis and cartilage resorption. Mechanistic studies showed that TNFα induced Fas expression within chondrocytes; however, the degree to which chondrocyte apoptosis is mediated by TNFα alone or dependent on the induction of Fas is unclear. This question was addressed by assessing fracture healing in Fas‐deficient B6.MRL/Faslpr/J mice. Loss of Fas delayed cartilage resorption but also lowered bone fraction in the calluses. The reduced bone fraction was related to elevated rates of coupled bone turnover in the B6.MRL/Faslpr/J calluses, as evidenced by higher osteoclast numbers and increased osteogenesis. Analysis of the apoptotic marker caspase 3 showed fewer positive chondrocytes and osteoclasts in calluses of B6.MRL/Faslpr/J mice. To determine if an active autoimmune state contributed to increased bone turnover, the levels of activated T cells and Treg cells were assessed. B6.MRL/Faslpr/J mice had elevated Treg cells in both spleens and bones of B6.MRL/Faslpr/J but decreased percentage of activated T cells in bone tissues. Fracture led to ∼30% to 60% systemic increase in Treg cells in both wild‐type and B6.MRL/Faslpr/J bone tissues during the period of cartilage formation and resorption but either decreased (wild type) or left unchanged (B6.MRL/Faslpr/J) the numbers of activated T cells in bone. These results show that an active autoimmune state is inhibited during the period of cartilage resorption and suggest that iTreg cells play a functional role in this process. These data show that loss of Fas activity specifically in chondrocytes prolonged the life span of chondrocytes and that Fas synergized with TNFα signaling to mediate chondrocyte apoptosis. Conversely, loss of Fas systemically led to increased osteoclast numbers during later periods of fracture healing and increased osteogenesis. These findings suggest that retention of viable chondrocytes locally inhibits osteoclast activity or matrix proteolysis during cartilage resorption. © 2014 American Society for Bone and Mineral Research.